Dastāvez : muṣannifīn ke apne qalam se (Uttar Pradesh Urdū Akādmī, 1983)
Autobiographical notices by the Urdu authors who were awarded prizes by the Uttar Pradesh Urdū Akādmī (state government Urdu academy)